Cornel Bierens : Schildpad met Roos en Mes. - Bierens, Cornel; Vereniging Vrienden van Abbemuseum, Eindhoven (Rotterdam : NAI Uitgevers, 2002)
Abramovic, Marina ; Appel, Karel ; Baselitz, Georg ; Beuys, Joseph ; Broodthaers, Marcel ; Christo ; Cragg, Tony (Anthony) ; Daniels, René ; Dibbets, Jan ; van Doesburg, Theo ; Dubuffet, Jean ; Duchamp, Marcel ; Riverhead (New York) ; Fontana, Lucio ; Gilbert & George ; van Gogh, Vincent ; Hockney, David ; Kandinsky, Wassily ; Kiefer, Anselm ; Klee, Paul ; Kosuth, Joseph ; Kruyder, Herman ; LeWitt, Sol ; Long, Richard ; Lüpertz, Markus ; Matisse, Henri ; Merz, Mario ; Moholy-Nagy, Laszlo ; Mondriaan, Piet ; Muñoz, Juan ; Penck, A.R. ; Picasso, Pablo ; Rainer, Arnulf ; Man Ray ; Richter, Gerhard ; Ryman, Robert ; Segantini, Giovanni ; Stella, Frank ; Ulay ; Warhol, Andy ; van Warmerdam, Marijke ; Willink, Carel
Nederlands
boek